Cloud and Payment Systems Under Siege: A Deep Dive into FBot Malware - Premanand Narasimhan; Dr.N.Kala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
FBot, a sophisticated Python-based malware, poses a significant threat to cloud services and payment systems. This article explores its architecture, capabilities, and operational patterns, analyzing how it exploits misconfigurations, payment vulnerabilities, and third-party dependencies. Through mapping with frameworks like MITRE ATT&CK and CAPEC, and leveraging AI-powered defense strategies, this study provides insights for cybersecurity teams, highlighting the necessity of proactive measures and robust risk management. Case studies illustrate the organizational impact and underscore the importance of enhanced policies to combat such evolving threats.